Implementation of an hybrid machine learning methodology for pharmacological modeling - Kwiatkowska, Katarzyna Malgorzata (2017)
Tese de mestrado, Bioinformática e Biologia Computacional (Bioinformática) Universidade de Lisboa, Faculdade de Ciências, 2017